Analisis Model Inquiry Training untuk Meningkatkan Kemampuan Berpikir Kritis Pembelajaran IPA pada Siswa Kelas V di SDN 122366: Analysis of Inquiry Training Model to Improve Critical Thinking Skills in Science Learning in Grade V Students at SDN 122366 - Desy Crismas Silaban; Delila Damanik; Purnama Silvia Br Sembiring; Leka Oktaviana Nababan (ITScience (Information Technology and Science), 2024)
Science is one of three subjects tested as a national standard exam for the elementary school level. Science learning is not only oriented towards knowledge, but it also has an important connection with the daily life of every living thing and the environment. Science is expected to be a vehicle for students to learn about themselves, the environment, and prospects for further development and apply them in their daily lives. This study aims to determine the learning outcomes of students in science after using the inquiry training model and its application in class V SDN 122366 Pematangsiantar. This research was conducted in September 2024 on teachers and students of class V SDN 122366 Pematangsiantar City. This qualitative research uses the Classroom Action Research (CAR) method. The learning instruments in this study consisted of the syllabus, lesson plans, and student worksheets. Data collection techniques used tests, observations, and interviews. Based on the test results in each cycle, the results showed that student scores increased, namely before applying the inquiry training model at the pre-cycle stage 53.44 with a percentage of completion of 12.5% ??included in the less category. At the cycle one stage after applying the inquiry training model, the average score of students was 69.37, with a percentage of completion of 43.75% in the sufficient category.Furthermore, at the cycle II stage, students' average score was 80, with a completion percentage of 87.5% in the outstanding category. Learning has achieved completion through the established success indicators. Student activity also increased; in cycle I, it was 45.31%, and in cycle II, it was 71.87%.